Determining the Level of Hospitalized Patients Satisfaction of Hospitals: A Systematic Review and Meta-Analysis - M Moosazadeh; M Nekoei-moghadam; MR Amiresmaili (Tehran University of Medical Sciences, 2013)
Background: Patients are the raison d'etre of the hospitals therefore satisfying their needs and expectations is one of the most important duties of the hospitals. Consequently in recent decades patient satisfaction has been considered as a reliable measure for studying the quality of care and treatment. Hence in the present study, documents related to patient satisfaction in Iran was surveyed and the overall level of satisfaction was estimated using meta-analysis.Materials and Methods: Articles on patient satisfaction were identified by searching different data bases using appropriate key words. Twenty six studies were extracted after applying inclusion criteria measures. The results were analyzed using Meta-analysis commands in STATA11 software.Results: 14058 cases were surveyed in this 26 studies by meta- analysis. Based on the random-effect model the patient overall satisfaction percentage was estimated at 70.5 (CI:63.3-77.6) though based on fixed effect model.Conclusion: The scale of patient satisfaction in Iran is in a proper level compared to other countries. Additionally, there has been an increasing trend in patient satisfaction in recent years, which might be attributable to measures such as using different methods of quality improvement, customer orientation and customer reverence.